An overview of researches on cheeses ripening in animal skin - Milna Tudor Kalit; Samir Kalit; Jasmina Havranek (Mljekarstvo)
The aim of this paper is to review the existing knowledge of manufacturing procedures, chemical composition, sensory attributes, biochemistry and microbiology of different kind of cheeses which ripen in the animal skin. These kinds of cheeses are produced in Croatia, Bosnia and Herzegovina, Montenegro and Turkey and there are few differences in the manufacturing procedure between them. The main specificity of these cheeses is ripening in a sack made of the whole lamb or goat body skin. Two or three months of anaerobic ripening in the skin gives the cheese markedly piquant taste and flavour. These cheese characteristics originate from intensive lipolysis and proteolysis. According to the content of moisture in the non fat solids and fat in total solids, cheeses in a sack belong to the group of hard or semi hard, full-fat or low-fat cheeses.